Penggunaan Flipbook “Project My Imboost” untuk Meningkatkan Kegiatan Literasi - Sumiatun, Sumiatun (Jurnal Didaktika Pendidikan Dasar, 2025)
This study aims to describe the steps of using the Project My ImBoost flipbook for learning to increase literacy and improve students’ writing skills portfolio in class 5B SDN Blimbing 3 Malang. Research methods using PTK consisting of two cycles. Cycle 1 was implemented in learning theme 6 Indonesian language content on paragraph material and cycle 2 on science content on heat and its transfer. The measurement used observation and a cheklist of student activeness in sending the writing skills portfolio. The findings show that the urgency of involving parents in literacy activities supports the success of student’s writing. The results of the portfolio of students’ writing skills in cycle 1 showed that 59% of students wrote in a coherent, 56% of students used letters according to PUEBI, 54% of students used effective sentences. Meanwhile, cycle 2 showed that 97% of students were active in literacy activities. Student portofolio writing actifity 88% of students have shown a coherent flow, 79% use letters according to PUEBI and 76% use effective sentences. The conclusion achievements in cycle 1 and cycle 2 shows an increase in the number of students in literacy activities 67%. The student portfolio in writing with a coherent flow 29%, using letters according to PUEBI 23% and using effective sentences 22%.